Technical Papers and Notes - Institute of Metals Division - The Role of Rate-History Effects in the Calculation of Creep Behavior - J. D. Lubahn (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1959)
Prior tests by Dorn, where the strain rate in a tensile test was suddenly changed, have shown a small, but definite rate-history effect to exist. If this effect is neglected in the calculation of creep behavior from tensile results, an error should occur. This paper shows that this error is smaller than experimental scattering, and may be neglected. DORN1 has found a small but definite rate-history effect in the aluminum alloy 250 at liquid-nitrogen temperature using tensile tests with an abrupt rate change. Such an effect is to be expected from pre-viously known2-6 temperature-history effects, together with general experience that effects produced by changing the strain rate a large amount are simi-